English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-02 11:16:12 · 6 answers · asked by awww 2 in Science & Mathematics Mathematics

h(x)=2(x-1)^5/3+5(x-1)^2/3

2006-11-02 11:17:14 · update #1

6 answers

Assuming this one is like your other questions, then
Assuming h(x) = f(g(x)), then
g(x) = x-1 and f(x) = 2x^5/3 + 5x^2/3

2006-11-02 11:18:43 · answer #1 · answered by MsMath 7 · 2 0

Well, I just took a test similar to this and I am guessing that this problem is like one of the problems I just had. I am assuming this is right:

f(x) = 2x^5/3 + 5x^2/3 test

2006-11-02 19:31:03 · answer #2 · answered by tiffyswig 1 · 1 0

h(x) = 2(x - 1)^(5/3) + 5(x - 1)^(2/3)
h(x) = ((x - 1)^(2/3))(2(x - 1) + 5)
h(x) = ((x - 1)^(2/3))(2x - 2 + 5)
h(x) = ((x - 1)^(2/3))(2x + 3)
h(x) = (2x + 3)(x - 1)^(2/3)

Now just plug in for x

2006-11-02 19:54:38 · answer #3 · answered by Sherman81 6 · 0 0

h(x)=2(x-1)^5/3+5(x-1)^2/3
h(x)=(2(x-1)+5)(x-1)^2/3
h(x)=(2x+3)(x-1)^2/3

...simplified, not solved.

2006-11-02 19:30:51 · answer #4 · answered by Helmut 7 · 0 1

You do the hokey pokey and then....you shake it all around.

2006-11-02 19:20:10 · answer #5 · answered by Anonymous · 0 2

um shouldnt u kno this since u learned it?

2006-11-02 19:18:02 · answer #6 · answered by <3Chrisssie 2 · 0 3

fedest.com, questions and answers